Efficacy and Safety of Camrelizumab Monotherapy and Combination Therapy for Cancers: A Systematic Review and Meta-Analysis - Wang, Jiting; Su, Song; Li, Jun; Li, Yaling (Frontiers in Oncology, 2021)
Objective This meta-analysis compared the safety and efficacy of camrelizumab monotherapy and combination therapy, aiming to provide a reference for the clinical combined use of camrelizumab in the treatment of cancers and also provide a reference for the development of subsequent indications of camrelizumab. Methods Meta-analysis was used to analyze the four eligible literatures. Primary endpoints of effectiveness index were objective response rate (ORR), progression-free survival (PFS), control rate (CR). Primary endpoint of safety index was rating of severity of adverse drug reactions (grades 1–5). Results The ORR, PFS, and CR values of combined treatment with camrelizumab was better than alone treatment, camrelizumab alone was better than chemotherapy (RR = 0.45; 95% CI, 0.30–0.67; P < 0.001; RR = 1.63; 95% CI, 1.25–2.13; P < 0.001; RR = 0.73; 95% CI, 0.52–1.02; P<0.001). When grade > 2, the incidence rate of combined treatment and chemotherapy are higher than monotherapy (RR = 0.66; 95% CI, 0.51–0.86; P<0.001). In any grade, the safety of camrelizumab combination therapy was better than that of monotherapy, the safety of chemotherapy was better than camrelizumab plus chemotherapy. Conclusion In terms of effectiveness, the combination of camrelizumab is better than monotherapy, and monotherapy is better than chemotherapy. In terms of safety, when the grade > 2, single use is better than combination therapy and chemotherapy. In any grade of adverse event, the safety of combined use of camrelizumab is better than that of single use, and the safety of chemotherapy is better than the combined use of camrelizumab plus chemotherapy.